Mindfulness: Age and gender differences on a Bosnian sample - Alispahic, Sabina; Hasanbegovic-Anic, Enedina (Psychological thought, 2017)
The goal of this research was to examine age and gender differences in mindfulness on Bosnian general population. The study was conducted on a sample of 441 participants from the general population, from twelve cities in Bosnia and Herzegovina. As a measure of mindfulness we used Five Factor Mindfulness Questionnaire. Results showed that older participants’ scores were higher than for younger participants for all aspects of mindfulness. There was found a statistically significant difference between the three age groups on the subscales of Acting with awareness F(2, 435) = 7.39, p < . 01 and of Non-judging of inner experience F(2, 428) = 5.67, p < . 01. We found statistically significant difference for the Acting with awareness between 20-32 age group (M = 28.57, SD = 5.66) and 33-49 age group (M = 31.01, SD = 5.00, t(292) = -3.91, p < .001), and between 20-32 age group and 50+ group (M = 30.14, SD = 5,86, t(290) = -2.32, p < .05). Also, there was a significant difference for the Non-judging between 20-32 age group (M = 24.77, SD = 5.80) and 33-49 age group (M = 26.65, SD = 5.09, t(288) = -2.94, p < .01), and between 20-32 age group and 50+ group (M = 26.49, SD = 4.90, t(287) = -2,71, p < . 05). According to the t-test results, there was statistically significant gender difference between the subscales Observing (t(432) = -2.259, p < .05) and Acting with awareness (t(432) = 2.197, p < .05), women scored higher than men on the subscale Observing, while men exhibited higher scores on the subscale Acting with awareness. Results of this research showed that there were found significant age and gender differences for some aspects of mindfulness in the sample of Bosnian general population.